Effect of Thermal Radiation on Heat Transfer of Ferrofluid Over a Stretching Cylinder with Convective Heating - Gangadhar, K.; Keziya, K.; Rushi Kumar, B. (International Journal of Engineering and Technology, 2018)
In view of this we scrutinize the numerical solution using the Kellor box method for the natural differential equations which describes the MHD flow of ferrofluid over a stretching cylinder with thermal radiation and convective heating. Water as convectional base fluid containing nano particles of magnetite (Fe3O4) is taken up. Comparison between magnetite (Fe3O4) and non-magnatic (Al2O3) nanoparticles is also made. The relevant physical parameters appearing in velocity and temperature distributions are analyzed and examined with the help of Fig.s. To examine the correctness of the method an anology has been made with some earlier published results. It is noticed that by increase the strength of magnetic field, the percent difference in the heat transfer rate of magnetic nano particles with Al2O3 decrease. Further, convective heating and thermal radiation are highly influenced the temperature distribution of the ferrofluid.Â Â